2017
DOI: 10.1093/cid/cix244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Integrated Antibiotic Allergy Testing Program on Antimicrobial Stewardship: A Multicenter Evaluation

Abstract: An integrated AAT-AMS program was effective in both de-labeling of AALs and promotion of improved antibiotic usage and appropriateness, supporting the routine incorporation of AAT into AMS programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
117
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 41 publications
1
117
0
2
Order By: Relevance
“…3, 4, 15 A better measure of the impact of patient-reported antibiotic allergy (so-called antibiotic allergy labels [AALs]) on prescribing is an assessment of antibiotic appropriateness, recent evidence demonstrating such a negative association. 16–18 Li et al . demonstrated also that a penicillin allergy was associated with a 1.82–2.58 fold increase in total antibiotic costs.…”
Section: Introductionmentioning
confidence: 99%
“…3, 4, 15 A better measure of the impact of patient-reported antibiotic allergy (so-called antibiotic allergy labels [AALs]) on prescribing is an assessment of antibiotic appropriateness, recent evidence demonstrating such a negative association. 16–18 Li et al . demonstrated also that a penicillin allergy was associated with a 1.82–2.58 fold increase in total antibiotic costs.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce inappropriate hospital antibiotic prescription by frequent antibiotic prescribers, we developed a centralised multidisciplinary antibiotic allergy testing program integrated within our AMS program at Austin Hospital and the Peter MacCallum Cancer Centre. After introducing the program, we found that 83% of patients could have an antibiotic allergy label removed 21 . This finding has particular significance as 48% of patients were immunocompromised, with conditions and treatments including haematological and oncological malignancy, autoimmune disease, solid organ or stem cell transplants, and steroid usage of more than 15 mg daily for 1 month 21 .…”
mentioning
confidence: 97%
“…After introducing the program, we found that 83% of patients could have an antibiotic allergy label removed 21 . This finding has particular significance as 48% of patients were immunocompromised, with conditions and treatments including haematological and oncological malignancy, autoimmune disease, solid organ or stem cell transplants, and steroid usage of more than 15 mg daily for 1 month 21 . After testing in this cohort, guideline‐preferred antibiotic prescribing significantly improved (95% [3 months after implementation] v 62% [3 months before implementation]), as did antibiotic appropriateness (adjusted OR, 12.27; 95% CI, 5.00–30.09) 21 .…”
mentioning
confidence: 99%
See 2 more Smart Citations